Beckman Brochure Describes New L7-55 Ultracentrifuge - Eastman, Elke (1985)
The press release announces a brochure devoted to the Model L7-55 Ultracentrifuge.
Keywords: Marketing; Scientific apparatus and instruments; Centrifuges; Beckman Instruments, Inc.